Manajemen Program Unggulan Tahfidz Qur’an dalam Meningkatkan Kualitas Hafalan Al-Qur’an Siswa - Dewi Rustiana; Muhammad Anas Ma`arif (Kharisma: Jurnal Administrasi dan Manajemen Pendidikan, 2022)
The purpose of this article was to determine how the process of planning, organizing, implementing, and evaluating improving the quality of student memorization in the tahfidz Qur'an program at MA NU NAFA. This research was a type of qualitative research with a case study approach. The subjects in this research were the headmaster, the head of the curriculum, the tahfidz coordinator, the tahfidz teachers, and the students in the tahfidz Qur'an program. The data collection techniques were carried out through observation, interviews, and documentation. The data analysis used interactive techniques by Miles and Huberman. The triangulation technique is used to check the validity of the data. The results of this research indicated that in the program of Tahfidz Qur'an, good management was carried out in supporting each program implementation process by following the goals and targets that have been set. The management of the tahfidz Qur'an program at MA NU NAFA was: The planning was carried out includes, including program planning that discussed costs and budgets, then educator planning and material planning. The organization was carried out in the preparation of the organizational structure by following the responsibilities and job descriptions. The implementation of the program was carried out through the learning process of the tahfidz Qur'an. The evaluation program was carried out in several ways or stages of the learning process that have been set.